2016
DOI: 10.1053/j.gastro.2016.09.064
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Ligands in Cigarette Smoke Induce Production of Interleukin-22 to Promote Pancreatic Fibrosis in Models of Chronic Pancreatitis

Abstract: BACKGROUND & AIMS Cigarette smoke has been identified as an independent risk factor for chronic pancreatitis (CP). Little is known about the mechanisms by which smoking promotes development of CP. We assessed the effects of aryl hydrocarbon receptor (AhR) ligands found in cigarette smoke on immune cell activation in humans and pancreatic fibrosis in animal models of CP. METHODS We obtained serum samples from patients with CP treated at Stanford University hospital and healthy individuals (controls) and isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 41 publications
4
75
0
4
Order By: Relevance
“…Interestingly, a recent paper showed that smoking, through interaction with the aryl hydrocarbon receptor on T cells, also stimulated PaSCs to promote fibrosis through the IL-22-pathway [66]. These findings again reveal an important interplay between inflammatory cells and PaSCs in CP pathogenesis.…”
Section: Mechanisms and Potential Of Therapeutics Developmentmentioning
confidence: 83%
See 1 more Smart Citation
“…Interestingly, a recent paper showed that smoking, through interaction with the aryl hydrocarbon receptor on T cells, also stimulated PaSCs to promote fibrosis through the IL-22-pathway [66]. These findings again reveal an important interplay between inflammatory cells and PaSCs in CP pathogenesis.…”
Section: Mechanisms and Potential Of Therapeutics Developmentmentioning
confidence: 83%
“…Other studies have reported increases in matrix metalloproteinase-9 (MMP-9) [68], tumor necrosis factor-α (TNF-α) [68], and soluble fractalkine [69]. Interestingly, IL-22 has also shown to be increased in CP patients who are smokers [66]. Thus, more studies are needed to identify, verify, and validate novel clinical biomarkers of disease activity to aid in early diagnosis of CP.…”
Section: Diagnosis Of Chronic Pancreatitismentioning
confidence: 99%
“…28 A recent report demonstrated that AhR ligands promote fibrosis in a mouse model of chronic pancreatitis. 29 …”
Section: Resultsmentioning
confidence: 99%
“…40 In a chronic pancreatitis model, AhR activation in T cells elicited IL-22 secretion associated with promotion of the fibrotic pancreatic stellate cell phenotype. 29 Given the robust activation of AhR by smoking compounds in acinar as well as immune cells, the specific role of AhR on adaptive/inflammatory responses in different cell types participating in smoking-related pancreatic disorders deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IL-22, a cytokine of the IL-10 family typically produced by CD4 + T cells (often together with IL-17), has been found to be secreted in response to Aryl hydrocarbon receptor (AhR) signaling and to promote tissue repair following acute pancreatitis in mice [64]. By contrast, chronic intraperitoneal administration of AhR ligands in mice with chronic pancreatitis has been shown to lead to high IL-22 production by CD4 + T cells, as well as PSC activation, in addition to exacerbated inflammation and fibrosis [65]. Interestingly, previous work examining Th17 cells in pancreatic oncogenesis also found elevated levels of IL-22 in PDAC-infiltrating CD4 + T cells, suggesting that IL-22 may be contributing to PDAC fibro-inflammatory reaction and might constitute a link between smoking and other activators of AhR signaling, chronic pancreatitis, and PDAC [60].…”
Section: Tissue Stress Inflammation and Carcinogenesismentioning
confidence: 99%